From a Parliamentary Assembly to a European Parliament: An Unfinished Process - Ioana Antoaneta Dodi (CES Working Papers, 2016)
The Parliamentary Assembly of the European Communities was the precursory body of the European Parliament, but it lacked the legitimacy the latter would gain starting with 1979, the year when the first European elections were held. The two entities differ in many ways, such as the internal organization, the competences and the connections with other European institutions, but the fundamental difference is the one that also determined the rest of the previously mentioned aspects, specifically the way their members were appointed. Although this aspect may seem solved, it will not be so until the suffrage for the European Parliament will not only be direct, universal and secret, but also accessible, assuring all interested stakeholders the same fair conditions for participation, thus eliminating all formal and informal obstacles for independent or party candidates.
Keywords: 330; political parties; elections; democratic deficit; discourse construction; ideology